2020
DOI: 10.1007/s12035-020-01873-x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Influence of apoE on Aβ43 Aggregation and Reduced Vascular Aβ43 Toxicity as Compared with Aβ40 and Aβ42

Abstract: The amyloid-β 43 (Aβ43) peptide has been shown to be abundantly expressed in Alzheimer's disease plaques, whereas only relatively low levels have been demonstrated in cerebral amyloid angiopathy (CAA). To better understand this discrepant distribution, we studied various biochemical properties of Aβ43, in comparison with Aβ40 and Aβ42. We assessed the interaction of Aβ43 with the three apoE isoforms (apoE2, apoE3, and apoE4) using SDS-PAGE/Western blotting and ELISA, aggregation propensity using thioflavin T a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 82 publications
1
7
0
Order By: Relevance
“…Doxycycline induced adipocyte specific NaKtide expression in these WD fed mice significantly attenuated the Iba1-positive microglia in the hippocampus ( Figure S3 ). These findings were consistent with the plasma levels of amyloid beta-40 (Aβ-40), a marker of cognitive decline ( Jakel et al., 2020 ; Rosu et al., 2020 ; Tsai et al., 2021 ; Watt et al., 2020 ), which showed significant increases in the WD fed mice ( Figure 3 F). The increase in Aβ-40 levels was significantly attenuated by doxycycline induced NaKtide expression ( Figure 3 F).…”
Section: Resultssupporting
confidence: 82%
“…Doxycycline induced adipocyte specific NaKtide expression in these WD fed mice significantly attenuated the Iba1-positive microglia in the hippocampus ( Figure S3 ). These findings were consistent with the plasma levels of amyloid beta-40 (Aβ-40), a marker of cognitive decline ( Jakel et al., 2020 ; Rosu et al., 2020 ; Tsai et al., 2021 ; Watt et al., 2020 ), which showed significant increases in the WD fed mice ( Figure 3 F). The increase in Aβ-40 levels was significantly attenuated by doxycycline induced NaKtide expression ( Figure 3 F).…”
Section: Resultssupporting
confidence: 82%
“…Unfortunately, age at onset, gender and APOE genotype could not be used as covariates in the analysis, because the number of mutation carriers was not sufficient for the statistical test. Our pilot study is nevertheless relevant because it highlights the involvement of Aβ 1-43 in AD and adds missing information regarding specific mutations to very recent studies published during these last 2 years [23,25,48]. As CSF Aβ 1-43 has never been studied before in CSF of APP and PSENs mutation carriers, the results need to be interpreted with caution and more studies are needed to replicate these findings in larger cohorts.…”
Section: Limitationsmentioning
confidence: 82%
“…2; Table 2). However, a recent study showed a reduced influence of APOE on Aβ 1-43 aggregation in cerebrovascular cells [48].…”
Section: Mutation Screeningmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, the use of ALEX-FCCS and FCS in this work highlights how single-molecule fluorescence techniques can be used to uncover molecular mechanisms that relate to the onset and progression of diseases associated with amyloid fibril formation. Elucidating the details of these dynamic biomolecular associations is not possible using post-mortem tissues from patients [207] , [208] .…”
Section: Studying the Interaction Of Aggregates With Other Proteins Using Fluorescence-based Single-molecule Techniquesmentioning
confidence: 99%